Rethinking tank rehabilitation: issues in restoring old tanks to their original state in irrigation structure - International Water Management Institute (International Water Management Institute, 2003)
Approaching the rehabilitation of the 50-100 year-old irrigation tanks?spread across Rajasthan, South Bihar, Madya Pradesh, Tamil Nadu, Karnataka, Andhra Pradesh, and other South Asian locations such as Sri Lanka?solely from an irrigation perspective, runs the risk of depriving communities of valuable socio-ecological services and functions that these structures provide today. These tanks may have become ?inefficient? in their original function of providing flow irrigation, but as they have degraded over time, they have evolved into valuable systems that support people?s livelihoods in a number of ways. In addition to storing water for crop irrigation, tanks provide services such as recharge of groundwater used by adjacent communities, fertile silted soil that allows cultivation of additional crops, fishing and aquaculture, water for raising livestock, and sand and soil used by small industries.